Clinical management of chronic hepatitis B: A concise overview. Issue 1 (30th November 2021) - Furquim d'Almeida, Arno; Ho, Erwin; Van Hees, Stijn; Vanwolleghem, Thomas
Abstract: Worldwide, over 250 million people are chronically infected with the hepatitis B virus (HBV). Infected patients have an up to 100‐fold increased risk for liver‐related complications, including cirrhosis, hepatic decompensation and hepatocellular carcinoma. Nonetheless, the majority of the infections remains asymptomatic, stressing the importance of HBV screening and linkage to care. Excellent clinical outcomes are seen during nucleos(t)ide analogue (NA) therapy, which often is continued indefinitively due to a lack of functional cure. Increasing evidence suggests that NA discontinuation following long‐term treatment induced viral suppression in patients without a functional cure may be a favourable option. Reliable biomarkers are, however, urgently needed to select the patients that would benefit from NA withdrawal. In addition, renewed and novel approaches to improve screening and linkage to care are other fundamental factors in the optimisation of the clinical management of chronic hepatitis B.